Physicochemical characteristics and SPME-GC-MS based volatilomics for discrimination of beef and pork patties - Rusydah, Muthia Kautsar; Indrasti, Dias; Budi, Faleh Setia; Regiyana, Yane; Rohman, Abdul; Dachriyanus; Abu Bakar, Nor Kartini; Yuliana, Nancy Dewi (jurnal1, 2025)
Beef is the preferred main ingredient for patties due to its high nutritional value; however, it is also a costly commodity. As a result, beef is often adulterated or partially substituted with pork, which can raise ethical and religious concerns. This study aimed to investigate the physicochemical and volatilome characteristics of patties made from beef, pork, and their mixtures at varying ratios, both with and without added seasonings (salt, pepper, and garlic). Physicochemical properties—including proximate composition, water-holding capacity, cooking loss, texture, and color—were analyzed to assess how pork and seasoning additions influence the characteristics of beef patties. Volatilome analysis was performed using solid-phase microextraction (SPME) coupled with gas chromatography–mass spectrometry (GC-MS). Data were analyzed using principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) to identify volatile compounds affected by the inclusion of pork. The results showed that adding 25% pork and seasoning altered the physicochemical properties of beef patties. These additions also affected the volatilome profiles. Key volatile marker compounds identified included Dimethyl disulfide (beef patties), Naphthalene (mixed patties), and Hexanal (pork patties) in seasoned samples. For unseasoned samples, potential markers were 3,7,11- Trimethyl-1-dodecanol, Hexadecane, and Nonanal for beef patties; Naphthalene, Octanal, and Heptanal for mixed patties; and Hexanal, (E)-2-Octenal, (E)-2-Heptenal, and 2-Pentylfuran for pork patties. These findings demonstrate that both physicochemical and volatilomic analyses are effective tools for distinguishing between patties made from beef, pork, and their mixtures. Future studies should evaluate whether these compositional changes influence the sensory properties of the patties. As a chemical validation, quantification of the identified markers using reference compounds is also required.